2017
DOI: 10.1016/j.bbamem.2017.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of 2-hydroxy arachidonic acid in a rat model of transient middle cerebral artery occlusion

Abstract: Stroke modifies the composition of cell membranes by eliciting the breakdown of membrane phospholipids whose products, such as arachidonic acid (AA), are released in the cytosol. The action of enzymes such as cyclooxygenases on AA leads to inflammatory stimuli and increases the cell oxidative stress. We report here the neuroprotective effect of 2-hydroxyarachidonic acid (2OAA), a cyclooxygenase inhibitor derived from AA, as a promising neuroprotective therapy against stroke. The effect of a single dose of 2OAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Previous studies allow us to estimate that we could detect changes at p ≤ 0.05 level with a statistical power of ≥ 80% with n ≥ 5 rats/ group (Llorerente et al ; Llorerente et al ; Anuncibay‐Soto et al ; Ugidos et al ; Anuncibay‐Soto et al ). Thus, prior to experimental procedure, the number of animals to be used in each group was established in five.…”
Section: Methodsmentioning
confidence: 92%
“…Previous studies allow us to estimate that we could detect changes at p ≤ 0.05 level with a statistical power of ≥ 80% with n ≥ 5 rats/ group (Llorerente et al ; Llorerente et al ; Anuncibay‐Soto et al ; Ugidos et al ; Anuncibay‐Soto et al ). Thus, prior to experimental procedure, the number of animals to be used in each group was established in five.…”
Section: Methodsmentioning
confidence: 92%
“…Accordingly, 2-hydroxy arachidonic acid (2-OAA) is a rationally designed derivative of AA known to be a competitive inhibitor of COX-1 and COX-2, and thus, it can be used in LPS-treated mice to decrease proinflammatory cytokines in serum (reviewed in [212]). When assessed for the treatment of stroke using S-D rats, 2-OAA treatment in the first hour of reperfusion after the stroke produced a neuroprotection [213]. At the molecular level, 2-OAA decreased phospholipase A2 (PLA2) in the cell membrane with a subsequent decrease in FFA release.…”
Section: Protein-lipid Interactions In Cardiovascular Diseases (Cvds)mentioning
confidence: 99%
“…A decrease in oxidative stress also occurs upon 2-OAA treatment in the first hour of reperfusion after stroke. Thus, the use of rationally designed lipids would seem to be a promising new stroke therapy, with an important advantage that they cross the Blood-Brain Barrier [213].…”
Section: Protein-lipid Interactions In Cardiovascular Diseases (Cvds)mentioning
confidence: 99%
“…The Sal treatment included antiinflammatory changes that suggested that its combination with anti-inflammatory agents could result in positive synergic effects against stroke. In this regard, the neuroprotective effect of some anti-inflammatory agents such as meloxicam or 2-OAA has been proved in global and other cerebral brain ischemia models (Llorente et al, 2015;De los Reyes and Céspedes 2014;Ugidos et al, 2017). The development of preferential COX-2 inhibitors such as "coxibs" has resulted in surprisingly different effects, making it necessary to test for each coxib member the risks and benefits in each application (Cairns, 2007).…”
Section: Looking For a Synergic Effect Against Strokementioning
confidence: 99%
“…In fact, a primary contribution of COX-1 and a delayed contribution of COX-2 in the progression of the damage have been reported in a global cerebral ischemia model (Candelario-Jalil et al, 2003). Thus, the use of NSAIDs with activity against COX-1 and COX-2, which have proved to have a strong neuroprotective effect in tMCAO models, has been claimed (Candelario-Jalil and Fiebich, 2008;Ugidos et al, 2017). Traditional NSAIDs seem to be able to balance the inhibition of the synthesis of platelet tromboxane (anti-trombotic activity) and the synthesis of prostacyclin in endothelial cells (prothrombotic activity).…”
Section: Glia the Nvu And Imbalance In The Activity Of Cox Isoformsmentioning
confidence: 99%